2012
DOI: 10.1007/s00280-012-1833-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-platinum regimens of gemcitabine plus docetaxel versus platinum-based regimens in first-line treatment of advanced non-small cell lung cancer: a meta-analysis on 9 randomized controlled trials

Abstract: GD acquired similar survival with platinum-based regimens in first-line treatment of advanced NSCLC. Platinum-based regimens had an advantage in TTP and ORR with more grade 3–4 nausea/vomiting, anemia, neutropenia and febrile neutropenia compared with GD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…In terms of the association between dose of thalidomide and effect, when Hoang et al . [24] increased the dose from 100 mg/day up to 1000 mg/day it did not seem more effective, which was consistent with other studies investigating the dose response relationship in multiple myeloma [31] and small-cell lung cancer [32, 33]. Regarding grade 3–4 toxicity data, our pooled analysis showed that the addition of thalidomide to chemotherapy or chemo-radiotherapy did not increase bone marrow toxicity such as leucopenia or neutropenia but induced a higher rate of grade 3 or greater non-hematologic toxicities including dizziness, constipation, rash and thromboembolic events.…”
Section: Discussionsupporting
confidence: 87%
“…In terms of the association between dose of thalidomide and effect, when Hoang et al . [24] increased the dose from 100 mg/day up to 1000 mg/day it did not seem more effective, which was consistent with other studies investigating the dose response relationship in multiple myeloma [31] and small-cell lung cancer [32, 33]. Regarding grade 3–4 toxicity data, our pooled analysis showed that the addition of thalidomide to chemotherapy or chemo-radiotherapy did not increase bone marrow toxicity such as leucopenia or neutropenia but induced a higher rate of grade 3 or greater non-hematologic toxicities including dizziness, constipation, rash and thromboembolic events.…”
Section: Discussionsupporting
confidence: 87%
“…Non small cell lung cancer (NSCLC) is the leading cause of cancerrelated deaths worldwide and although several active anticancer agents are available, platinum-based chemotherapy is still the standard first-line therapy for patients with metastatic or recurrent disease, achieving better response and progression free survival than non platinum-containing regimens [1].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the efficacy and safety of taxanes in combination with other third-generation chemotherapy agents such as gemcitabine and vinorelbine have also been assessed [31][32][33][34][35] .…”
Section: Taxanes In Combination With Other Thirdgeneration Chemotheramentioning
confidence: 99%